The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1194/jlr.r200018-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Natural genetic variation as a tool in understanding the role of CETP in lipid levels and disease

Abstract: Since the identification of cholesteryl ester transfer protein (CETP), its role in the modulation of HDL levels and cardiovascular disease has been debated. With the early detection of genetic variants followed by the finding of families deficient in CETP, genetic studies have played a large role in the attempts to understand the association of CETP with lipids and disease; however, results of these studies have often led to disparate conclusions. With the availability of a greater variety of genetic polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
117
3
5

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(135 citation statements)
references
References 115 publications
10
117
3
5
Order By: Relevance
“…In contrast, the present results are consistent with our recent meta-analysis, which showed that throughout a large number of studies in both healthy and diseased populations, CETP gene variants associated with decreased CETP activity also were associated with elevated HDL-C levels. 35 This observed correlation is also consistent with the fact that individuals with genetic CETP deficiency invariably present with high HDL-C levels 36 -38 and with the fact that pharmacological CETP inhibition raises HDL-C levels. 10 -12 …”
Section: Cetp Plasma Levels and Hdl-c Levelssupporting
confidence: 73%
“…In contrast, the present results are consistent with our recent meta-analysis, which showed that throughout a large number of studies in both healthy and diseased populations, CETP gene variants associated with decreased CETP activity also were associated with elevated HDL-C levels. 35 This observed correlation is also consistent with the fact that individuals with genetic CETP deficiency invariably present with high HDL-C levels 36 -38 and with the fact that pharmacological CETP inhibition raises HDL-C levels. 10 -12 …”
Section: Cetp Plasma Levels and Hdl-c Levelssupporting
confidence: 73%
“…As the result, CETP protein mass in the medium and the transcripts from transfected cell had not significantly changed compared to those of wild-type cell (supplemental fig.1), and it suggests that c.658G>A mutation caused abnormal splicing but it does not have a missense effect. Subject 3 had also I405V polymorphism as the heterozygote, but it was reported that the effect of I405V as 405VV homozygote for plasma CETP protein level by meta-analysis was -0.19 μg/mL less [21]. I405V polymorphism would decrease CETP mass in subject 3 slightly, but c.658G>A…”
Section: Discussionmentioning
confidence: 95%
“…Circulating CETP levels are highest in K629 CETP CC allele carriers (14,(16)(17)(18), whereas both GH and glucocorticoids are able to reduce serum CETP (7,8,20). The increase in HDL-C after GH replacement in glucocorticoid-treated hypopituitary patients homozygous for the K629 CETP CC allele may thus be explained in part by assuming that GH elicits a more pronounced decrease in circulating CETP levels in these patients.…”
Section: Discussionmentioning
confidence: 95%
“…Consequently, increased CETP activity results in a lower HDL-C (11)(12)(13). Common genetic variations have been identified in CETP (14,15), among which the K629 CETP COA promoter polymorphism (rs1800775) has been shown to regulate CETP transcriptional activity in vitro (16). The more frequent C allele is associated with higher circulating CETP mass and activity and a lower HDL-C (17,18).…”
Section: Introductionmentioning
confidence: 99%